Effects of phosphorus supplementation upon the performance of West African Dwarf lambs - Kabaija, E.; Smith, O.B. (1987)
Evaluates the need for phosphorus supplementation in West African Dwarf lambs fed on hay, the typical dry-season feed of tropical livestock. Presents data on the composition of concentrate supplements, weight gains and feed consumption, changes in liveweight gains and serum inorganic phosphorus with and without P supplement, ash, calcium, phosphorus & magnesium content of the ribs and femurs, and quality characteristics of the humerus bone.